Pengembangan Media Pembelajaran Berbasis Macromedia Flash 8 dalam Upaya Meningkatkan Efektifitas Belajar Ilmu Pengetahuan Sosial - Ongku Desix B. Harahap (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
The aims of this study were to produce and to find out the effectivity of using the Macromedia Flash Profesional 8-based learning media as well. The type of this study was a Research and Development model adopted from ADDIE. The steps of ADDIE model were including Analyze, Design, Develop, Implement, and Evaluate. The trial subjects consisted of material experts of social science, learning design experts, learning media experts, three students of individual trial, nine students of small group trial, and also thirty students of main field trial. The data about the quality of this product was collected by using questionairres. The data was collected and analyzed by qualitative descriptive analysis. The results of Macromedia Flash Profesional 8-based learning media on the subject material of local environmental maps showed that:  the validation of the entire material experts showed that the media was extremely good (96.47%); the validation of the entire design experts showed that the media was extremely good (91.81%); the validation of learning media was extremely good (90.00%); the validation of individual trial was extremely good (88.59%); the validation of small group trial was extremely good (91.75%); and the validation of main field trial was extremely good (95.76%). Based on the result of hypothetical test proved that there was a significant difference between students’ learning  taught by Macromedia Flash Profesional 8  conventional learning.